Circulating trophoblast numbers as a potential marker for pregnancy complications. (2nd July 2022) - Crovetti, Brielle; Maktabi, Mohamad Ali; Erfani, Hadi; Panchalee, Tachjaree; Wang, Qun; Vossaert, Liesbeth; Van den Veyver, Ignatia
Abstract: Objective: To explore the potential of circulating trophoblasts (TBs) as a non‐invasive tool to assess placental health and predict obstetric complications. Methods: We retrospectively reviewed maternal characteristics and pregnancy outcomes of 369 women who enrolled in our original cell‐based NIPT (cbNIPT) study. The number of circulating TBs recovered from the maternal blood samples was recorded and expressed as fetal cell concentration (FCC). We evaluated if FCC can be used to predict pregnancy outcomes such as hypertensive disorders of pregnancy (HDP), fetal growth restriction, placental abruption, preterm labor, and pregnancy loss. Results: Receiver operating characteristic (ROC) analysis was performed to find the best cut off value to classify FCC into a low and high FCC group, and this cut‐off point was calculated as 11.1 cells per 100 ml of blood. The adjusted odds ratio (aOR) for the composite morbidity was significantly increased for the high FCC group at an aOR of 1.6. Conclusion: Circulating TB have the potential of predicting obstetrical complications such as HDP. Future studies, with larger sample sizes, should focus on the study of these cells as a biomarker for placental health and a possible screening or diagnostic tool for fetal genetic conditions. Key Points: What is already known about this topic? Isolation and genetic analysis of circulating trophoblasts is explored for non‐invasive prenatal diagnosis. The number of recovered trophoblasts is variable and can be affected by factors such as maternal body mass index and gestational age. What does this study add? We investigated if the number of recovered trophoblasts correlates with other maternal and obstetric characteristics. Recovery of more circulating trophoblasts correlates with a composite of various pregnancy complications.